The impacts of the food, fuel and financial crises on households in Nigeria: A retrospective approach for research enquiry - Blessing M. Chiripanhura; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
This paper examines the impacts of the financial, food and fuel crises on the livelihoods of low-income households Nigeria. It uses primary household level data from Nigeria to analyse the impacts of induced price variability on household welfare. Our results indicate that aggregate shocks have significant adverse effects on household consumption, human capital, and labour decisions with a degree of impact variability between northern and southern regions of the country. We find that the coping strategies adopted by the poor to deal with the short-term effects of the crises, and which include substitution for lower quality food, increasing the intensity of work, withdrawing children from school - especially girls - and engaging children in child labour, can lock households in a low-income equilibrium or poverty trap. Provided that covariate shocks exacerbate these effects, tackling the effects of covariate risks becomes central for present and future development policy.
Keywords: I2; I3; O1; O5; 330; food; fuel; financial crisis; poverty; vulnerability; sub-Saharan Africa; Nigeria; Lebensmittelpreis; Kraftstoff; Preis; Finanzkrise; Armut; Nigeria